3D Facial Reconstruction from Point Clouds with Hermite Radial Basis Functions and Multilevel Partition of Unity - Tubone, Guilherme Hideo (2024)
Point cloud surface reconstruction is the process of transforming raw data from 3D scanners into a digital representation of an object surface. This process has applications in various fields, and as a result, many methods have been proposed to solve this problem over the years. In this work, we focus on methods that generate surfaces represented as level sets of implicit functions. Specifically, we propose a method based on Hermite Radial Basis Functions (HRBF) with Multilevel Partition of Unity (MPU). The HRBF allows a precise and detailed representation of the surface geometry, even when dealing with nonuniform data, while the MPU enables a efficient and adaptive reconstruction process. To demonstrate the efficacy of our method, we applied it to a dataset of human faces. The results show that the method can successfully reconstruct the facial geometry, capturing details of the surfaces.